HADIS TEMATIK TENTANG CYBERBULLYING: Integrasi Pendekatan Psikologis dalam Upaya Pencegahan - Raihan, Nur; Wildan, T (Islamijah: Journal of Islamic Social Sciences, 2024)
Cyberbullying is growing along with the rapid development of technology and social media, which has an impact on the mental health of victims. This study aims to analyse thematic traditions related to social ethics and respect in Islam and integrate psychological approaches for Cyberbullying prevention. Using a qualitative method of analysis, this study identifies traditions that teach the importance of maintaining honour and the prohibition of harming others. The psychological approach used includes the impact of Cyberbullying on mental health, such as anxiety and depression, as well as prevention strategies, such as increasing empathy and self-control. The integration between Islamic teachings and psychology offers a comprehensive preventive solution to create a healthier digital environment. The results show that the integration of thematic hadith about Cyberbullying with a psychological approach provides a comprehensive solution to prevent Cyberbullying through strengthening moral values and building mental resilience based on Islamic teachings.